Transgenerational and Intergenerational Family Trauma in Colm Tóibín’s The Blackwater Lightship and “Three Friends” - Jose M. Yebra (Moderna Språk)
This article analyses Colm Tóibín's The Blackwater Lightship (1999) and his short story "Three Friends" (2006), which are the testimony of the changes affecting current Ireland, especially those concerning the roles and engagement between females and gays. Drawing on Abraham and Torok's The Shell and the Kernel (1994), my main contention is that Tóibín's texts explore the trans-generational transmission of trauma and memory in an Irish context. Also Grabriele Schwab's Haunting legacies (2010), which explains the transference and haunting of trauma from both Holocaust victims and perpetrators to their descendants, will give a fuller understanding of The Blackwater Lightship and "Three Friends". I will demonstrate that different generations of Irish women, or Irish women and their (gay) sons hurt one another, being both victims and perpetrators. This paper also analyses the effectiveness of the language of trans/inter-generational memory and conflict, especially when paradoxically transmitted through strategic silences and meaningful gaps. Thus, Tóibín's texts look at the past and how it is codified and transmitted at a family level to eventually herald a message of renewal.